1956
DOI: 10.1037/h0040073
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus sequence and concept learning.

Abstract: This study is concerned with rules for arranging stimulus information to facilitate concept learning. The rules that gain support may not apply to all concept learning situations, but are expected to be applicable to situations in which the following four conditions obtain. These are: (a) S must learn several concepts; (b) each stimulus item is a positive instance of one concept and a negative instance of all alternative concepts; (c) every stimulus item is a compound of several variable components, only one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 1 publication
3
19
0
Order By: Relevance
“…Also, boys learned more from the programmed instruction than the girls did. Detambel and Stolurow (1956) found that variations in sequence can differentially aid the lower ability college students, permitting those in the lowest quintiles to achieve scores indistinguishable from the students in the highest quintile. Eigen (1962) found that with eighth graders who were learning mathematics there also was a significant interaction between IQ and the "method" used.…”
Section: Instructional Programmentioning
confidence: 96%
“…Also, boys learned more from the programmed instruction than the girls did. Detambel and Stolurow (1956) found that variations in sequence can differentially aid the lower ability college students, permitting those in the lowest quintiles to achieve scores indistinguishable from the students in the highest quintile. Eigen (1962) found that with eighth graders who were learning mathematics there also was a significant interaction between IQ and the "method" used.…”
Section: Instructional Programmentioning
confidence: 96%
“…These include, for example, content structure and redundancy (Bryan and Harter 1899;Anderson 1983), distinctions between nominal stimulation and internal representations (Fechner 1860, Hull 1943Rothkopf 1957;Underwood 1963), the consequences of active engagement (Gates 1917;Hovland et al 1949), techniques to foster attention and engagement (Rothkopf and Bloom 1970;Hyde and Jenkins 1973;Scardamalia et al 1984), the interval between instructive events (e.g., Ebbinghaus 1885; Smith and Rothkopf 1984;Dempster 1996;Pashler and Bayliss 1991;Pashler et al 2003), evocation schedules (Bjork 1988), sequence of presentation in induction (e.g., Detambel and Stolurow 1956;Rothkopf 1958), the role of surface context (Ross 1984;Rothkopf et al 2002), as well as a number of others. The literature is very large, and its interpretation and use for practical applications in teaching designs allows for many possibilities.…”
Section: Goals Of Instructional Researchmentioning
confidence: 98%
“…Regarding differences in aptitudes, studies by Detambel and Stolurow (1956), Ferster and Sapon (1958); Gagne (1962), all report no significant correlations between aptitude and achievement in programmed learning when gain score is used.…”
Section: Research Evidencementioning
confidence: 99%